2003
DOI: 10.1161/01.str.0000096540.40826.ba
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between p38 Mitogen-Activated Protein Kinase and Caspase-3 in Cerebral Endothelial Cell Death After Hypoxia-Reoxygenation

Abstract: Background and Purpose-The emerging concept of the neurovascular unit in stroke reemphasizes the need to focus on endothelial responses in brain. In this study we examined the role of mitogen-activated protein (MAP) kinase signaling in the regulation of hypoxic cell death in cerebral endothelial cells. Methods-Human cerebral microvascular endothelial cells were exposed to 4 to 12 hours of hypoxia followed by 12 to 24 hours of reoxygenation. Cytotoxicity was measured by quantifying lactate dehydrogenase release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 41 publications
(33 reference statements)
2
42
1
Order By: Relevance
“…As one example, it has been demonstrated that caspase-3 may mediate cleavage of upstream MAP kinase MEKK1, leading to a constitutively active fragment that not only activates p38-MAPK, but also may play a role in NF-B signaling (5,40). As another example, a role for DNA repair enzyme poly(ADP-ribose) polymerase-1 (PARP-1) in NF-B signaling has been shown in multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…As one example, it has been demonstrated that caspase-3 may mediate cleavage of upstream MAP kinase MEKK1, leading to a constitutively active fragment that not only activates p38-MAPK, but also may play a role in NF-B signaling (5,40). As another example, a role for DNA repair enzyme poly(ADP-ribose) polymerase-1 (PARP-1) in NF-B signaling has been shown in multiple studies.…”
Section: Discussionmentioning
confidence: 99%
“…c-jun NH 2 -terminal kinase was reported to mediate Fas-induced apoptosis in neuronal cells (39), and p38 MAPK has certain cytoprotective effects in nonneuronal cells (40). The activation of the ERK pathway by growth factors often stimulates cell differentiation, mitosis, and hypertrophy (41); ERK MAPK also phosphorylates caspase-9 at Thr125 resulting in the inhibition of caspase-9 processing and caspase-3 activation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, p38/MAPK mediates cytotoxicity in the endothelial cells (Lee, Lo 2003), and together with ERK1/2, can mediate secretion of MMP-9 in neuronal-astrocytic co-cultures (Wang et al, 2002).…”
Section: Discussionmentioning
confidence: 99%